2023
DOI: 10.3390/foods12091842
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Potential Application of 3D Food Printing to Enhance Elderly Nutritional Dietary Intake

Abstract: The contradiction between the growing demand from consumers for “nutrition & personalized” food and traditional industrialized food production has consistently been a problem in the elderly diet that researchers face and discuss. Three-dimensional (3D) food printing could potentially offer a solution to this problem. This article reviews the recent research on 3D food printing, mainly including the use of different sources of protein to improve the performance of food ink printing, high internal phase emul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 95 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…Specifically, the SCOBY 1:0.33 formulations, which contained wheat flour, demonstrated lower values of the flow behaviour index ( n ) compared to the SCOBY 1:0.25 formulations. This outcome was attributed to the presence of starch in wheat flour, acting as a plasticizing agent that enhanced material fluidity, flowability and printing performance (Xie et al , 2023). Additionally, the consistency index ( k ) values indicated that pure SCOBY does not fall within the printable range.…”
Section: Results and Analysismentioning
confidence: 99%
“…Specifically, the SCOBY 1:0.33 formulations, which contained wheat flour, demonstrated lower values of the flow behaviour index ( n ) compared to the SCOBY 1:0.25 formulations. This outcome was attributed to the presence of starch in wheat flour, acting as a plasticizing agent that enhanced material fluidity, flowability and printing performance (Xie et al , 2023). Additionally, the consistency index ( k ) values indicated that pure SCOBY does not fall within the printable range.…”
Section: Results and Analysismentioning
confidence: 99%
“…The BMI serves as an initial indicator of excess body mass index above 25 [1], and a BMI over 30 kg/m 2 indicates obesity [31]. In other references, whereby the existence of certain groups/subgroups in the observed dataset will be evident [33], regardless of the age group starting from childhood [34], over adulthood [35], to the elderly [1,36], visualizations of the distribution and changes were observed. In this paper, in Figure 1, visualizations of the distribution and changes were observed through different phases of the ketogenic diet and in two groups, male and female.…”
Section: Applicationsmentioning
confidence: 96%
“…Similarly, other 3D-printed meat products for people with swallowing difficulties also include pureed chicken and tuna [111]. When it In summary, the 3D printing technique has attracted a significant amount of attention in food production for its advantage of freedom to design novel structures and textures and to develop personalized nutrition and flavors [119,120]. Also, mechanized production simplifies and speeds up the manufacturing process, in addition to reducing food waste [101,105].…”
Section: Designing Food Texture With 3d Printingmentioning
confidence: 99%
“…Kersiene et al [126] prepared a stable double emulsion with several bioactive substances (adding vitamins B6, B12, and C and anthocyanins in the aqueous phase and vitamins A and D3 in the oil phase) for formulations tailored to the elderly, which showed that the encapsulated compounds were stable and such active substances could be released during digestion. Xie et al [120] considered that 3D food printing is crucial to meet requirements for the elderly regarding energy supplementation (protein enrichment and fat reduction), flavor regulation, and nutrition balance. Their review demonstrated that the addition of whole eggs, whey protein, oats, and peanuts in 3D-printed food increased the nutritional profiles.…”
Section: Nutrition and Sensory Improvement In Tmfmentioning
confidence: 99%